A robust and reliable non-invasive test for stress responsivity in mice - Zimprich, Annemarie; Garrett, Lillian; Deussing, Jan M.; Wotjak, Carsten T.; Fuchs, Helmut; Gailus-Durner, Valerie; de Angelis, Martin Hrabě; Wurst, Wolfgang; Hölter, Sabine M. (Frontiers in Behavioral Neuroscience, 2014)
Stress and an altered stress response have been associated with many multifactorial diseases, such as psychiatric disorders or neurodegenerative diseases. As currently mouse mutants for each single gene are generated and phenotyped in a large-scale manner, it seems advisable also to test these mutants for alterations in their stress responses. Here we present the determinants of a robust and reliable non-invasive test for stress-responsivity in mice. Stress is applied through restraining the mice in tubes and recording behavior in the Open Field 20 minutes after cessation of the stress. Two hours, but not 15 or 50 minutes of restraint lead to a robust and reproducible increase in distance travelled and number of rearings during the first five minutes in the Open Field in C57BL/6 mice. This behavioral response is blocked by the corticosterone synthesis inhibitor metyrapone, but not by RU486 treatment, indicating that it depends on corticosteroid secretion, but is not mediated via the glucocorticoid receptor type II. We assumed that with a stress duration of 15 minutes one could detect hyper-responsivity, and with a stress duration of two hours hypo-responsivity in mutant mouse lines. This was validated with two mutant lines known to show opposing effects on corticosterone secretion after stress exposure, corticotropin-releasing hormone (CRH) over-expressing mice and CRH receptor 1 knockout (KO) mice, which both showed the expected phenotypes. It is possible to repeat the acute stress test several times without the stressed animal adapting to it, and the behavioral response can be robustly evoked at different ages, in both sexes and in different mouse strains. Thus, locomotor and rearing behavior in the Open Field after an acute stress challenge can be used as reliable, non-invasive indicators of stress responsivity and corticosterone secretion in mice.